Evaluation of antimicrobial efficacy of Miswak on Oral Bacteria - Fakhri F. Algedaimy; Ibtesam O. Amer; Jomana Amer; Amna Mohamed; Ghada M. Salem (المجلة الأفروآسيوية للبحث العلمي, 2024)
Maintaining oral hygiene through regular removal of dental plaque and deposits is essential for preventing dental caries. Oral hygiene practices vary across different populations, societies, and cultures. Despite the widespread use of toothbrushes and toothpaste, this study aimed to assess the antimicrobial activity of the miswak chewing stick in vivo on oral bacteria. The study involved volunteers using fresh miswak for 6 minutes, with saliva samples (2 ml) collected before and after use by expectorating into a sterile glass test tube. The results showed a significant decrease in the total number of surviving bacterial colonies in the saliva samples, with mean bacterial counts of 286,816.3 ± 535.5524 (n=50) before and 153,020.4 ± 391.1782 after using the miswak. This reduction was statistically significant (p = 0.000535). It can be concluded that using miswak has beneficial effects such as antiseptic, antimicrobial, anticariogenic, and analgesic properties. it is recommended to encourage the use of miswak as part of daily oral hygiene routines alongside toothbrushes and toothpaste and incorporate the use of miswak into school health programs to foster healthy habits among children from an early age.